Very-Long-Chain Resorcinolic Lipids of Ailanthus altissima Samaras - Elżbieta G. Magnucka; Robert Zarnowski; Przemysław Bąbelewski (Molecules)
Two new very-long-chain 5-n-alkylresorcinol (AR) homologues, that is, 5-n-nonacosylbenzene-1,3-diol and 5-n-hentriacontylbenzene-1,3-diol, were isolated from acetone extracts of Ailanthus altissima samaras. These phenolic compounds were detected in nearly equal proportions, although their total content varied considerably between samples from urban-grown trees. No correlation was observed between AR levels and the physiological state of the tree, suggesting that environmental conditions may strongly influence AR biosynthesis in A. altissima. Furthermore, the isolated AR mixture exhibited antifungal activity against soil-borne phytopathogens of the genera Fusarium and Rhizoctonia.